Understanding Public Attitude towards Political Candidate through Conversational Network in West Java Regional Election - Rimba Pratama Putra; Hanif Fakhrurroja; Andry Alamsyah (Journal of Data Science and Its Applications, 2019)
Social media is a very important part of the political campaign strategy. By using information about various policies as well as public opinion, will provide rich information in political issues during elections. The problem is how political attitudes in social media relate to the results of the election winners. In this paper, we proposed a methodology of social network analysis to measure conversational network activity. As a case study, we select the Pilkada Jawa Barat 2018 for the reason most populous province in Indonesia. We get the conversation in online social network service Twitter and collected 70335 tweets from June 20 to June 26, 2018. Our findings indicate that the network properties of each candidate is in accordance to the real count and the candidate that appear most often are "@ridwankamil", the name of the winner of the regional elections in the Pilkada Jawa Barat 2018. We summarize all the conversations of each candidate and our results show there are high correlations with the results of the election winners. Because the higher the conversations network of each candidate, the greater the possibility of winning the election.